Pharmacokinetic and pharmacodynamic responses in adult patients with Chagas disease treated with a new formulation of benznidazole - Fernández, Marisa Liliana (2016)
Fil: Fernández, Marisa Liliana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.